2000
DOI: 10.1002/1099-0518(20010101)39:1<216::aid-pola240>3.0.co;2-z
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of star-shaped polystyrenes via nitroxide-mediated stable free-radical polymerization

Abstract: High molecular weight star‐shaped polystyrenes were prepared via the coupling of 2,2,6,6‐tetramethyl‐1‐piperidinyloxy (TEMPO) terminated polystyrene oligomers with divinylbenzene (DVB) in m‐xylene at 138 °C. The optimum ratio of the coupling solvent (m‐xylene) to divinylbenzene was determined to be 9 to 1 based on volume. Linear polystyrene oligomers (Mn = 19,300 g/mol, Mw/Mn = 1.10) were prepared in bulk styrene using benzoyl peroxide in the presence of TEMPO at approximately 130 °C under an inert atmosphere.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(37 citation statements)
references
References 22 publications
0
37
0
Order By: Relevance
“…The first report on the synthesis of star‐shaped polymers using NMRP can be dated back to 1997 by Solomon and co‐workers . Since then, several research groups have reported the preparation of star polymers by NMRP . For instance, Kuo and co‐workers reported the synthesis of a series of star block copolymers from POSS by core‐first NMRP .…”
Section: Polymerization Techniquesmentioning
confidence: 99%
“…The first report on the synthesis of star‐shaped polymers using NMRP can be dated back to 1997 by Solomon and co‐workers . Since then, several research groups have reported the preparation of star polymers by NMRP . For instance, Kuo and co‐workers reported the synthesis of a series of star block copolymers from POSS by core‐first NMRP .…”
Section: Polymerization Techniquesmentioning
confidence: 99%
“…[4] The in-line ATR-FTIR investigations of the carbonylation of epoxides and a mechanistic understanding of these processes were demonstrated by Allmendinger et al [5] Lizotte, Long and Pasquale et al presented the real-time monitoring of the radical polymerizations of acrylate systems and styrene and also the synthesis of maleic anhydride-cyclic olefin alternating copolymers. [6,11,12] Moreover, they calculated the monomer conversions and determined the kinetic data.…”
Section: Full Papermentioning
confidence: 99%
“…That's why the original second-order kinetic law is reduced to the pseudofirst-order kinetic law (1). [3,6,[10][11][12] À d½Conc dt ¼ k app ½Conc…”
Section: Ir Monitoringmentioning
confidence: 99%
“…The field of polymer synthesis has experienced revolutionary advances in the types and complexity of new synthetic techniques being developed for well‐defined macromolecules. These include the design and synthesis of single‐site metal catalysts for olefins;1–3 ring‐opening metathesis4–6 and ring‐opening polymerization (ROP);7–11 a variety of controlled free‐radical polymerization strategies, including atom transfer radical polymerization12–18 and nitroxide‐mediated19–24 and radical addition–fragmentation/transfer procedures;25–27 and dendritic macromolecules 28–35. With the exception of nitroxide‐mediated polymerization and purely organic approaches to dendritic macromolecules, these synthetic advances are based on organometallic catalysts.…”
Section: Introductionmentioning
confidence: 99%